Do aión ao eterno retorno, percursos com Giorgio Colli - Ancona Lopez, Chiara (2022)
This research presents the work of Giorgio Colli, a contemporary philosopher known mostly in European circles. Colli worked to reshape the perception of the work of F. Nietzsche in the world by creating the critical edition of his work and establishing the definitive text in German and Italian assisted by Mazzino Montinari. Colli’s philosophical-philological work provided for the first time the authentic Nietzschean text, in the totality and unity of the Complete Works in the chronological order as written by the German philosopher. The extent of his efforts to restore the original Nietzsche, however, limited the reach of his own philosophies. Assuming the parameters of the pre-Socratic Greeks, Colli guided his theoretical analysis and philosophical action between Dionysian and Apollonian targeting the knowledge as a way of living. His central publication, Philosophy of Expression, proposes an epistemology that traces the path of the logos to its origins and problematizes the formal logic in which the rationalization is structured, elaborating upon modal logic and contrasting mode and form and argues for a rationality linked to life. To highlight the character and ideas of the philosopher-philologist Giorgio Colli, this research presents a glimpse into his life, his wandering reason and work. We narrate the arduous path through the European editorial environment to publish the Works of Nietzsche in the rough political-ideological post-Second World War landscape. We review a few works and philosophers which Colli refers to constantly and critically throughout his philosophical, cultural, and academic work. From this philosophy linked to life, which does not make concessions to abstractions, we provide a critical view of the logical-rational thinking, contrasting effective results with results produced in modern life; we propose perspectives that intersect between the original Greek philosophers and the philosophy of marginalized cultures and people. The pathways show the decline of Western thinking and the possibilities of philosophy to change the outcome. This research is an invitation into Giorgio Colli’s philosophy and to follow the illuminated trail created by thinkers like himself towards philosophical knowledge as a way of living